Associations between OPG and RANKL polymorphisms, vertebral fractures, and abdominal aortic calcification in community-dwelling older subjects: the Sao Paulo Ageing & Health Study (SPAH). Issue 11 (November 2016) - Pereira, R.; Figueiredo, C.; Cha, C.; Caparbo, V.; Oliveira, R.; Franco, A.; Menezes, P.; de Castro, I.; Onuchic, L.
Abstract Summary This is the first study analyzing concomitantly osteoprotegerin (OPG )/ receptor activator of nuclear factor kappa B ligand (RANKL ) polymorphisms and OPG/RANKL serum levels and their association with bone mineral density (BMD), vertebral fractures, and vascular aortic calcification in a cohort of 800 subjects in community-dwelling older individuals. Introduction Osteoprotegerin (OPG) and RANKL play an important role in osteoclast activation and differentiation as well as in vascular calcification. At present, there are no studies ofOPG orRANKL gene polymorphisms in Brazilian older populations. The aim of this study was to evaluate OPG/RANKL polymorphism and their association with vertebral fractures (VFs) and aortic calcification. Methods Eight hundred subjects (497 women/303 men) were genotyped for theOPG 1181G>C (rs2073618), 163C>T (rs3102735), 245T>G (rs3134069), and 209G>A (rs3134070) andRANKL A>G (rs2277438) single-nucleotide polymorphisms (SNPs). VFs were evaluated by spine radiography (Genant's method). Aortic calcification was quantified using Kauppila's method. Results The isolated genotype analyses and single-allele frequency data showed association ofOPG 163C, 245G, and 209A alleles with presence of VFs (P < 0.05). Multiple logistic regression of subjects with absence of VFs vs. those with VFs (grades II/III) revealed onlyOPG 209A homozygosity as a risk factor for higher-grade VFs (odds ratio (OR) = 4.17, 95 % CI 1.03–16.93, P = 0.046). Regarding aortic calcification, the isolated genotype analysis frequency data revealed a significant association ofOPG 1181G, 163C, 245G, and 209A alleles with absent aortic calcification (P < 0.05). Multiple logistic regression data confirmed that theOPG 209A allele was protective for aortic calcification (OR = 0.63, 95 % CI 0.45–0.88, P = 0.007) and theOPG 1181C allele was a risk factor for aortic calcification (OR = 1.26, 95 % CI 1.00–1.58, P = 0.046). Conclusion This study showed that theOPG 209AA genotype was a risk factor for higher-grade VFs, theOPG 209A allele was protective for aortic calcification, and theOPG 1181C was a risk factor for aortic calcification, supporting the involvement ofOPG polymorphisms in the analyzed phenotypes and the concept that the related pathogenesis is multifactorial.